2016
DOI: 10.1016/j.rmed.2015.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Increased asthma and adipose tissue inflammatory gene expression with obesity and Inuit migration to a western country

Abstract: No association was found between gene expression of mast cell markers in adipose tissue and asthma. Among Greenlandic Inuit, adipose tissue inflammation is also increased in those who migrate to Denmark, possibly as a result of dietary changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 44 publications
(44 reference statements)
1
8
0
Order By: Relevance
“…MCs are increased in the white adipose tissue (WAT) of obese individuals, 46,47 and serum tryptase levels are increased in obese individuals 46 . MCs have been proposed as a potential cellular link between obesity and asthma, 48 although WAT MC‐related gene expression did not differ between asthma and non‐asthma in a study of Inuit residing in Denmark and Greenland, in contrast to IL‐6 mRNA which was increased in asthma WAT 49 . A link between obesity and airway MC activation in asthma may exist.…”
Section: Discussionsupporting
confidence: 84%
“…MCs are increased in the white adipose tissue (WAT) of obese individuals, 46,47 and serum tryptase levels are increased in obese individuals 46 . MCs have been proposed as a potential cellular link between obesity and asthma, 48 although WAT MC‐related gene expression did not differ between asthma and non‐asthma in a study of Inuit residing in Denmark and Greenland, in contrast to IL‐6 mRNA which was increased in asthma WAT 49 . A link between obesity and airway MC activation in asthma may exist.…”
Section: Discussionsupporting
confidence: 84%
“…In contrast, in populations with higher intake of n-3 PUFAs, such as Inuits, asthma prevalence is significantly reduced [204][205][206]. Inuits are indigenous population of arctic and sub-arctic regions of Greenland, Canada and Alaska, whose diet is based mainly on fish and arctic marine mammals and hence is enriched with n-3 PUFAs [207]. Interestingly, there is an association between genotype and disease development in geographically separate Inuit populations-one living in Greenland and the other, migrated to Denmark [208].…”
Section: Asthmamentioning
confidence: 99%
“…↓ Risk of asthma, rhinitis and aeroallergen sensitization [200,204,220,221] ↓ Asthma symptoms scores and ↓ responsiveness to acetylcholine [222] Improvement in pulmonary functions and ↓ use of short-acting inhaled bronchodilators and inhaled corticosteroids [290] ↑ Prevalence of wheeze [248] Adulthood ↓ Prevalence of asthma symptoms, airway hyperresponsiveness and ↑ asthma control and lung function [47,202,206,207,224,[226][227][228]230,233] ↓ Exhaled nitric oxide, ↓ serum eosinophils and ↑ FEV1 [225,229] ↓ Bronchodilator use, ↓ exhale nitric oxide and ↓ severity of exercise-induced bronchoconstriction [228,[231][232][233] Allergic Rhinitis Infancy and childhood ↓ Risk of rhinitis development [251,[254][255][256] Adulthood ↓ Prevalence [257,258] Atopic Dermatitis Pregnancy and lactation ↓ Incidence and intensity in the offspring [259,260]…”
Section: Asthmamentioning
confidence: 99%
“…The authors measured several inflammatory cytokines and concluded that diet/lifestyle changes led to modification of adipose tissue inflammation leading to asthma. 49 This same group has also shown that an "arctic" diet is associated with higher lung function and adds to the evidence that diet, which is linked to ethnicity, may influence lung outcomes. 50 The role of breastfeeding remains controversial.…”
Section: Metabolic and Nutritional Factorsmentioning
confidence: 81%